Comparative studies in Germanic syntax : from A(frikaans) to Z(urich German) - Hartmann, Jutta; Molnárfi, László, 1971- (Linguistik aktuell, 2006)
This selection of papers presented at the 20th Comparative Germanic Syntax Workshop brings together contributions that address issues in syntactic predication and studies in the nominal system, as well as papers on data from the history of English and German. Showing a strong comparative commitment, the contributions include studies on previously neglected data on case and predicative structures in Icelandic and other Germanic languages, on the (non- )syntactic distinction of predicative vs. argument NP/DPs, on quirky V2 in Afrikaans, the pronominal system, resumptive pronouns with relative cla.